Simplification of Teacher Aini's Novel by Andrea Hirata Based on the Theory of Structuralism Narrative Model Seymour Chatman - Sulistia Ellsa; Ida Zulaeha; Yusro Edy Nugroho (Universitas Negeri Semarang, 2024)
Learning Indonesian language in Higher Secondary School consists of the fields of language and literature. One of the activities of literary appreciation in schools is reading literature, but the restriction on literary reading material and the low interest of students in reading makes learning less optimal. Literary reading materials available in schools are novel forms that are considered less effective because they are too long and take a long time in reading. This research attempts to simplify the novel of Guru Aini by Andrea Hirata as well as his sympathy in the learning of Indonesian language. This research aims to uncover patterns and forms of simplification of Guru Aini novels as a means of strengthening learning reading literature based on the theory of narrative structuralism of the Seymour Chatman model. This research uses the Theory of Narrative Structuralization of the model of Seymor Chatman with a descriptive approach to analysis. The results of this research are a design of digital simplification novel of Professor Aini by Andrea Hirata with simplification events and exists in the novel. The findings in this study are a pattern of simplification based on the theory of the narrative structuralism of Seymour Chatman's model. The benefits of this research can provide new perspectives in the analysis of novel texts and the resulting simplification products can be a means of reading for teachers and learners in literary reading learning.